Study on Gas Control in Goaf of High Gas Coal Seam: A Case Study of Tingnan Coal Mine, China - Jiamei Chai (Geofluids)
When stratified mining is used in extrathick coal seam, the gas emission in goaf of the first mining face is large, and it is easy to cause gas overrun in the upper corner during the rapid advance of the working face, which seriously affects the safe and efficient mining of the working face. The gas drainage in goaf by roof high-drainage way is the fundamental solution to solve the gas overrun in the upper corner, and the reasonable layout position is related to the drainage effect of high-drainage way. In this paper, 206 slicing mining face of Tingnan Coal Mine in Binchang Mining Area of Shaanxi Province is taken as an engineering example. Theoretical analysis, fluent numerical simulation, and field verification are used to study and analyze the reasonable layout position and drainage effect of roof high-drainage way in working face. The research results show that the reasonable position of the high-drainage way layout is the horizontal distance of 15 m, the vertical distance of 21 m and 26 m, the horizontal distance of 25 m, and the vertical distance of 21 m and 26 m. In the layout position of 15 m horizontal and 21 m vertical, the gas drainage volume of high-drainage roadway is 16.4~23.3 m3/min, and the average gas drainage volume is 20.45 m3/min. The gas drainage volume of high-drainage roadway accounts for 52.1% of the gas emission, which achieves the expected effect and realizes the safety requirements of gas prevention and control in working face. The research results of this paper can provide guidance for the layout of high-drainage way in Tingnan Coal Mine and adjacent mines.